Dechlorinase activity and chlordane removal by Streptomyces strains as pure and mixed defined cultures - Fuentes, María Soledad (2013)
Chlordane (CLD) is a toxic fumigating agent widely used in the past, which is now found in air, soil and water resources. Technical chlordane consists in 147 components, and it has been included in the list of the 12 persistent organic pollutants of Stockholm Convention (2001) because of its persistence, toxicity and tendency to biomagnification. Bioremediation is an attractive cleaning technique of polluted environments. The use of actinobacteria for this purpose, results an effective biotechnological approach due to their metabolic versatility and furthermore their use in mixed cultures can increase the catabolic pathways available for biodegrading these contaminants. The aim of this work was to evaluate the chlordane removal capacity and dechlorinase activity by pure and mixed actinobacteria cultures, under controlled laboratory conditions, and to select one mixed culture for further morphological studies. Streptomyces spp. M7, A2, A5, A6, A13 previously isolated in the laboratory and Streptomyces coelicolor A3 (2) were cultivated individually in minimal medium (MM) with CLD for acclimation. These strains, as pure cultures and consortia from two to six microorganisms, were cultivated in MM with CLD (1.66 mg L-1). Microbial cells were used to obtain cell-free extracts for dechlorinase activity assays and the supernatants of these cultures were used to determine residual CLD by gas chromatography. The selected mixed culture according to their dechlorinase activity and capacity to remove CLD was grown in MM either with glucose or chlordane as carbon source and analyzed at 72 h in an optical microscope the probability of morphological changes. Dechlorinase activity ranged between 0.00 to 1291.28 mmolCl-/h/mg protein and CLD removal percentages was between 82.6 to 95.5%. The mixed culture consisting of Streptomyces sp. A2-A13-Streptomyces coelicolor A3(2) showed the best enzyme activity but not the minimal residual CLD concentration. Because no linear relationship between residual CLD and enzyme activity was obtained, the ratio between these two parameters was evaluated, and the mixed culture Streptomyces sp. A2-A5-A13 with the minimal obtained relationship was selected. In CLD presence, the microscopic analysis of this culture showed scarce vegetative cells and numerous spores, which results of the hyphal fragmentation. These Streptomyces strains were able to grow as mixed cultures, in CLD presence, and showed ability to dechlorinate and remove this toxic compound from the culture medium. Therefore the mixed culture of Streptomyces sp. A2-A5-A13 could be a promising tool for CLD biodegradation.